Developing a Support Website for Postsecondary Students with Learning Difficulties in Indonesia: “Students’ Go-To for Campus Life Support” - Dirgantara, Putri; Suyama, Natsuka; Inoue, Kaoru; Yamanishi, Yoko; Renhoran, Cahya Ramadani; Komariyah, Dwi Ayu Nur; Buwana HTN, Cahya; Fajariani, Dini; Sahid, Muhammad Hidayat; Saloko, Erayanti; Ito, Yuko (Indonesian Journal of Disability Studies, 2024)
Inclusive education has become increasingly common worldwide, even in higher education; however, the corresponding practical support in Indonesia is limited. Herein, a support website was developed for postsecondary students with learning difficulties vis-à-vis campus life in Indonesia. Web contents and information for supporting such students were developed from an occupational therapy perspective, including considering web accessibility and university lecturers’ opinion in Indonesia. After the feedback on the pre-launched version administered to current students in Indonesia, this new tool had a good level of satisfaction regarding the provision of support to such students’ academic activities on campus. However, information volume and display organization may require improvements in the future. Furthermore, the website could not only facilitate support for postsecondary students with learning difficulties in connection to the awareness of this area, which is limited in Indonesia, but also elucidate the role of occupational therapists.